ISLAMICATION EFFORTS IN LEARNING MATHEMATICS - Kidup Supriyadi (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2020)
This paper discusses efforts to Islamize science in mathematics learning. This paper focuses its study on descriptions of the Islamization of science and mathematics learning. The data sources in this article were obtained from scientific works that discuss the Islamization of science in mathematics learning. This main source is strengthened and supported by other relevant data (called secondary data), namely in the form of books or sources from other authors who talk about the Islamization of science in mathematics learning. This paper is a research library (library research) using a qualitative approach, which tries to describe a variable, symptom or situation as it is and is not intended to test certain hypotheses. The results of this paper show that the Islamization of science is carried out in an effort to rebuild the spirit of Muslims in developing science through freedom of intellectual reasoning and rational-empirical and philosophical studies while still referring to the contents of the Qur'an and the Prophet's Sunnah. So that Muslims will rise and advance to catch up with other people, especially the West. Efforts to Islamize science in knowledge have been developed by the thoughts of al-Attas and al-Faruqi regarding the idea of Islamization, according to him, science is not value-free but value requirements (value laden). Both also believe that the civilization brought by the West is a civilization that upholds the value of dichotomism. and this value is of course contrary to the existing values in Islamic teachings, namely monotheism. In developing integrated mathematics learning with Islam, the concept of learning must be based on the method of monotheism taught by the al-Qur'an.